Identifying detour patterns of rail feeder bus routes: A city-scale analysis - Enhui Chen; Zhitong Sun; Keyu Ji; Jing Teng (Journal of Transport Geography, 2026)

The role of arbuscular mycorrhizal fungi on ecosystem multifunctionality across phenological phases under warming in alpine meadows - Keyu Chen; Xiaoyue Yin; Luming Ding; Jingying Feng; Wubuli Subinuer; Changting Wang; Xinhua He; Chuangming Yang (CATENA, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Lithium-ion power batteries: From material performance to system-level safety and sustainability - Keyu Chen; JiaJia Luan; Brooke Xi; Weihua Zhang; Hanyu Jin; Daying Guo; Xi'’an Chen; Shun Wang (Chemical Engineering Journal, 2026)

Quantitative analysis of crust and loose layer characteristics on the surface of the earthen Great Wall - Keyu Wang; Wenwu Chen; Qiang Qi; Peiran Liu; Bobo Jia; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Impacts of herbaceous plant roots on the engineering properties and erodibility assessment of the ming great wall earthen sites in the alpine and humid-cold regions - Qiang Qi; Wenwu Chen; Keyu Wang; Xiaoxiao He; Ying Wang; Fuqiang Liu; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Towards complete utilization of rice husk components: A sequential process for the co-production of pectin, xylo-oligosaccharides, lignin-silica hybrid material, and fermentable sugars - Yuanxian Wu; Yuxin Xiao; Ronglian Hua; Keyu Chen; Yuanyuan Zhu; Junhua Zhang; Junjun Zhu (Biomass and Bioenergy, 2026)

Melatonin ameliorates manganese-induced neurological deficits in mice by inhibiting TXNIP signaling–mediated neuroinflammation and microglial pyroptosis: Role of SIRT6 - Jia Liu; Jixing Liang; Keyu Chen; Kuan Liu; Changjiang Yu; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2026)

Bioinspired artificial lipase with engineered hydrophilic microenvironment for oriented substrate binding and structured lipids preparation - Han Liu; Keyu Xing; Shaoyi Yu; Jia Tu; Yanna Jiao; Liguang Xu; Wei Chen; Pei Jia; Zhou Xu (Food Research International, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

Corrigendum to “The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence” Aquaculture, Volume 622, 15 July 2026, 744082 - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

The MPOA-VTA Pathway: From Pup Care to Adult Helping - Keyu Chen; Jingkai Fan; Han Xu (Neuroscience Bulletin, 2026)

The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

Novel inter-cable wire rope dampers for hanger cable vibration control: Experiment, FE modeling method, and Field test - Shilong Yang; Keyu Lai; Wei Fan; Yuling Liu; Zhiheng Chen; Zhengqing Chen (Engineering Structures, 2026)

Temperature-induced metabolic reconfiguration and community shifts reveal the mechanistic basis of cold inhibition on anammox consortia - Rongrong Chang; Jinluo Pang; Keyu Chen; Chaoxi Yang; Yamiao Yang; Baocheng Huang; Rencun Jin (ENGINEERING Environment, 2026)

Diagenetic evolution of clay minerals and impacts on reservoir quality of the Wufeng and Longmaxi Shale in Sichuan Basin of China - Yang Chen; Jianhua Zhao; Qinhong Hu; Keyu Liu; Mengxiang Yu; Wei Wu; Chao Luo (Applied Clay Science, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Functional repositioning of aerobic granular sludge as a nitrite-producing pretreatment for mainstream Anammox driven by slowly biodegradable organic matter - Zongshuo Han; Xiaoying Zheng; Jiaqing Tao; Yunqing Li; Keyu Chen; Ruijie Hu; Yifan Zhou; Yang Zhang (Process Safety and Environmental Protection, 2026)

A layered classification framework of near-infrared waste plastic identification through interpretable machine learning - Keyu Zhu; Junrong Chen; Ruizhe Tu; Changlin Cao; Weiming Zhou; Songwei Yang; Qingrong Qian; Qinghua Chen; Kunsen Lin (Journal of Environmental Chemical Engineering, 2026)

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Thresholds and shifting drivers for the temporal dynamics of mycorrhizal symbiosis in a temperate grassland - Qiang Dong; Xin Guo; Keyu Chen; Shijie Ren; Yu Tang; Xinling Dai; Yaoming Li; Jing Zhang; Baoming Ji (Plant and Soil, 2026)

Effects of aerosol decline on surface solar radiation during the implementation period of air pollution prevention and control policies over China - Keyu Zhao; Henan Han; Junyan Chen; Guozheng Liu; Tiegang Liu (Journal of Hazardous Materials, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Establishing tracer gas dilution as a potential reference method for in-stack CO2 emission metrology - Yayong Liu; Zhe Bi; Xiaoping Song; Chi Tu; Keyu Chen; Shao-Meng Li (Journal of Cleaner Production, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Low‑intensity aeration enhances algal–bacterial synergy to improve nitrogen removal from wastewater with low carbon-to-nitrogen ratio - Yunqing Li; Xiaoying Zheng; Ruijie Hu; Jiaqing Tao; Zongshuo Han; Keyu Chen; Yifan Zhou; Yang Zhang; Wei Chen (Bioresource Technology, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Spatiotemporal variations of rainfall interception before and after implementation of Grain for Green Program in the Loess Plateau - Junyan Chen; Guozheng Liu; Jing Wu; Keyu Zhao; Tiegang Liu (Journal of Hydrology, 2026)

Projecting shifts in drought-induced thresholds for wheat yield loss under climate change in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Fangzheng Chen; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (Agricultural and Forest Meteorology, 2026)

First Case of Nocardia seriolae Infection in China Cultured Channel Catfish ( Ictalurus punctatus ) - Mingqi Ai; Keyu Zhou; Qibin Jiang; Kun Peng; Yilin Wang; Yiteng Luo; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Journal of Fish Diseases, 2026)
Nocardia seriolae is a causative agent for fish skin ulcers and sarcoidosis, resulting in significant losses in both brackish and freshwater fish farming industries. From October to November 2023, channel catfishes ( Ictalurus punctatus ) cultured in Xiaowan reservoir at Dali city, Yunnan province in China, showed gross pathological changes with skin ulcers, white nodules in the liver and heart, histopathological tests revealed the typical granulomas and chronic hepatitis changes in the liver, and the clumps of filamentous bacteria in the heart and spleen. A Gram‐positive acid‐fast bacterium (CCF_NS01) was isolated from viscera (liver, spleen and kidney); biochemical tests and 16sRNA‐GyrB gene concatenated sequences analysis of this isolated microorganism identified it as N. seriolae . Drug sensitivity testing indicated susceptibility to commonly used antibiotics such as co‐trimoxazole, doxycycline, enrofloxacin, florfenicol, amikacin and rifampicin. In isolated CCF_NS01, multiple pathogenic factors corresponding to encoding genes were detected, including espG , mftF , pcaA , fadD32 , pks13 , narJ , feoB , sodA , katG and mceF . 100% mortality with 1 × 10 8 , 1 × 10 7 and 1 × 10 6 cfu/mL in a 35‐d challenge test period was observed, and the intraperitoneal injection median lethal dose (LD 50 ) was 1.89 × 10 4 cfu/mL. This is the first isolation report of N. seriolae infection from cultured channel catfish, aiming to warn against the continuous host‐range expansion of this pathogen, which is threatening the inland aquaculture industry.

Synthetic data augmentation and Integrated prediction framework for low-carbon recycled concrete: Leveraging CTGAN and multiple ML models stacking - Jinlong Liu; Shiqi Wang; Keyu Chen; Kun Wang; Yucheng Fan; Qinghe Wang (Journal of Cleaner Production, 2026)

Symbiotic food grade fermentation enhances the multifunctional photoprotective activity of Tricholoma matsutake through metabolic remodeling - Yongyan Pei; Zhiqing Tang; Keyu Lin; Hongliang Li; Yitong Chen; Hua Cao (Food Bioscience, 2026)

Future climate change increases the risk of wheat yield loss due to agricultural drought in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Shijin Yao; Siyi Li; Alfredo Huete; Yi Li; Qiang Yu (European Journal of Agronomy, 2026)

Smart optical imaging-assisted acoustic streaming enrichment system for targeted microalgae screening under multiple stress conditions - Yihan Ma; Longfei Chen; Yifan Wang; Tao Jiang; Chen Yang; Xiaotong Si; Yantong Liu; Keyu Chen; Fenghua Jiang; Chengjun Sun; Xuan Xiao; Yi Yang (Bioresource Technology, 2026)

The Role of Coagulation-Related Genes in Glioblastoma: A Comprehensive Analysis of the Tumor Microenvironment, Prognosis, and Treatment - Jingyi Yang; Lei Shen; Yuankun Cai; Ji Wu; Keyu Chen; Dongyuan Xu; Yu Lei; Songshan Chai; Nanxiang Xiong (Biochemical Genetics, 2026)

Antisolvent sequence as a tunable switch for zein-naringin-D-tocopheryl polyethylene glycol 1000 succinate (TPGS) nanoparticles: interfacial dynamics and bioactivity enhancement - Yitong Wang; Keyu Qiu; Ruizi Zhou; Shuxian Bai; Chao Ai; Yanan Zhao; Jesus Simal-Gandara; Hui Teng; Lei Chen (Food Chemistry, 2026)

Unraveling the drivers of corn yield response to optimization fertilization in plateau acidic red soils - Zhengfa Chen; Keyu Yan; Hui Yan; Xiaohan Mei; Chi Wang; Xingwei Chen; Wanli Hu; Bin Fu; Ming Ni; Zhiwu Li; Qingsong Duan; Yanmei Hu; et al. (Field Crops Research, 2026)

Lacustrine organic carbon burial in deep time: Perspectives from major geologic events and tectonic-climatic-ecological coupling - Chao Liang; Ao Chen; Yingchang Cao; Jing Wu; Yu Han; Keyu Liu; Guanghui Yuan; Fang Hao (Earth-Science Reviews, 2026)

Soft-chemical topotactic pathway to (001)-faceted hollandite K-Fe-Ti oxides with accelerated Li+ migration - Xing Wang; Ling Che; Zihao Li; Zhigao Chen; Xingang Kong; Kun Zhang; Keyu Xie (Chemical Engineering Journal, 2026)

Responses of Phytoplankton Bloom Magnitude Off the Yangtze River Estuary to the Zonal Position of the Northwest Pacific Subtropical High - Qiong Wu; Keyu Hu; Bo Li; Tianqi Xiong; Hui Chen; Shaofeng Wang (International Journal of Climatology, 2025)
The phytoplankton bloom magnitude (PBM) off the Yangtze River Estuary has important responses to the changes in the east–west position of the northwest Pacific subtropical high (NWPSH). The potential physical mechanism is analyzed through observations and a physical–biogeochemical model. Results reveal that the anomalously high precipitation in June–July increases the extension ranges of low salinity and high NO 3 concentration water in NWPSH westward extension years. However, due to persistent cloudy and rainy weather, the light condition is unfavorable for the explosive growth of phytoplankton. When the NWPSH moves northward in August, the study area is controlled by anomalously anticyclonic circulation; hot and sunny weather prevails, the nutrients carried by the Yangtze River discharge during the previous June–July period continue to extend toward Jeju Island with the diluted water, favoring the explosive growth of phytoplankton, and vice versa. Sensitivity experiments reveal that when the June–July averaged river discharge and nutrients in NWPSH westward extension years are twice those in normal years, the range of phytoplankton blooms in August can extend to 124.2° E. When the June–July averaged river discharge and nutrients in NWPSH westward extension years are only 0.5 times those in normal years, the range of phytoplankton blooms in August only extends to 123° E. Therefore, the changes in river discharge and nutrient expansion range caused by the east–west position changes of the NWPSH in June–July are important reference indicators for phytoplankton bloom variations throughout the summer. The study provides new scientific reference for seasonal phytoplankton bloom forecasting off the Yangtze River Estuary.

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Marine flooding induced basinal brine mixing and carbonate cementation: An example from Cretaceous ultra-deep clastic reservoirs in the Kuqa Depression, western China - Shunyu Wang; Jian Wang; Keyu Liu; Yong Li; Zhenkun Li; Meiyi Chen; Leilei Yang (Marine and Petroleum Geology, 2025)

Artificial perches improve the stability of soil microbial networks in degraded alpine steppe of Sanjiangyuan National Park - Yanhe Wang; Mingxin Yang; Keyu Chen; Dongzhi Huangqing; Shouxing Wang; Xiaochun Ning; Hongkui Yang; Qiang Gu; Huakun Zhou (Journal of Environmental Management, 2025)

Graphite-phase carbon nitride composites: Pioneering advancements and future prospects in capacitive desalination - Feifan Zhang; Hongying Lv; Yuying Pan; Yutao Chen; Keyu Hou; Zhiheng Wang; Jiuwen Sun; Hong Chen; Junli Pan; Shouqiang Huang (Journal of Environmental Management, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

Design of amides and long-chain alkyl alcohols for high selectivity recovery of titanium and iron from ilmenite - Keyu Zhu; Qinqin Yu; Guokang Hu; Changchang Chen; Yanni Li; Jiacan Tang; Weiwei Zhang (Minerals Engineering, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Regulation of astaxanthin accumulation in Phaffia rhodozyma under titanium dioxide and rapeseed oil stress by amino acid metabolism - Meizhen Liu; Tiantian Han; Lu Luo; Ying Zhang; Gaofeng Yuan; Xubo Fang; Keyu Dong; Jing Zhang; Xiaoe Chen (Food Chemistry, 2025)

Bouquet-like β-alanine modified Bi4O5Br2/Fe-CeO2 Z-scheme heterojunction photocatalyst for degradation of ciprofloxacin: potential application, toxicity evaluation and degradation mechanism - Yu Chen; Pengfei Zhu; Xuemei Chen; Xinglin Li; Keyu Pu; Jiayi Fan (Environmental Research, 2025)

Dynamic quantitative characterization method for the weathering degree of earthen heritage sites surfaces based on 3D scanning technology and wavelet transform theory - Wenwu Chen; Qiang Qi; Keyu Wang; Shuai Zhang; Zhiqian Guo; Kebing Ren; Haitao Yan (Bulletin of Engineering Geology and the Environment, 2025)

Phenotypic and transcriptomic insights into the antibacterial effects of magnolol against the novel pathogen Vibrio misgurnus - Keyu Zhou; Qibin Jiang; Bowen Huang; Kun Peng; Mingqi Ai; Le Xu; Songmao Wu; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture International, 2025)

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Transgenerational effects and mechanisms of nano-SiO2 on pulmonary - Jiangliang Chu; Chengzhi Liu; Shuang Chen; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan; Zhe Wang (Reproductive Toxicology, 2025)

Myricetin, as a potential new antiviral agent against Rana grylio ranavirus (RGRV) - Kun Peng; Silu Tian; Le Xu; Yu Yuan; Mingqi Ai; Qibin Jiang; Keyu Zhou; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Fish & Shellfish Immunology, 2025)

Morphology and in-situ sulfur isotope characteristics of pyrite across the Ordovician-Silurian boundary marine shale in South China: Indicative significance for sedimentary environment - Shichao Ji; Chao Liang; Yu Han; Qing Tang; Yingchang Cao; Keyu Liu; Jing Wu; Haoran Xie; Fanglu Chen (Marine and Petroleum Geology, 2025)

Excessive mitochondrial stress response triggers neuronal injury through the persistent eIF2α phosphorylation in mice exposed to manganese - Yunfei Jia; Bin He; Keyu Chen; Kuan Liu; Changjiang Yu; Bo Sun; Zhuo Ma; Bin Xu (Journal of Hazardous Materials, 2025)

Characterizing multi-scale heterogeneities in shales: An innovative workflow and application to Paleogene lacustrine shales in the Subei Basin, eastern China - Zongguang Guo; Keyu Liu; Lingjie Yu; Jie Chen; Yuqi Wu; Lei Chen; Chao Liang (Marine and Petroleum Geology, 2025)

Detection of toluene at ppb levels using Au catalyst supported on Al-doped ZnO - Jiali Hong; Keyu Chen; Kaiping Yuan; Mingyue Lin; Qi Cao; Jialong Lin; XinLin Wang; Xiaoqian Bai; Tamao Ishida; Toru Murayama; Guangli Xiu (Journal of Environmental Chemical Engineering, 2025)

Performance and mechanism of enhanced phosphorus release and volatile fatty acid production from Fe-P sludge via co-fermenting with agricultural wastes - Wei Yao; Rongrong Chang; Keyu Chen; Chaoxi Yang; Yan Lu; Shixu Wang; Kaiyue Dong; Baocheng Huang; Rencun Jin (Journal of Environmental Sciences, 2025)

Enhanced rare-earth doped mechanoluminescent piezoelectric heterojunction semiconductors through interface engineering with tunable photonic responses for advanced sensing applications - Fanlei Qin; Yujie Chen; Qinglong Hu; Keyu Han; Zhen Xiao; Yang Zhang; Gongxun Bai (Chemical Engineering Journal, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

Activation of the Nrf2 Signaling Pathway by Tetrahydroberberine Suppresses Ferroptosis and Enhances Functional Recovery Following Spinal Cord Injury - Xiang Li; Heng Yu; Rongjie Liu; Jiansen Miao; Junlei Lv; Shu Yang; Yuxuan Zhu; Yan Chen; Keyu Lu; Chongan Huang; Xiangyang Wang (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

A hybrid data-driven and physical model-based approach for predicting the mechanical properties of cable-arrays in flexible cable dual-AUVs systems - Kuo Chen; Zhier Chen; Jiancheng Yu; Kai Ren; Wenkang Jiao; Keyu Chen; Yu Tian; Jie Sun (Ocean Engineering, 2025)

Construction and efficacy of a recombinant QX-like infectious bronchitis virus vaccine strain - Lin Lin; Keyu Feng; Guanming Shao; Shiying Gong; Tongfei Liu; Feng Chen; Xinheng Zhang; Qingmei Xie (Virus Genes, 2025)

Joint optimization of AoI and energy for AUV-assisted data collection in underwater acoustic sensor networks - Weinan Cao; Keyu Chen; En Cheng (Frontiers in Marine Science, 2025)
Underwater data collection is a key component of ocean observation systems, providing reliable data provenance through sensor networks deployed across diverse marine environments. Timely and energy-efficient data collection mechanisms are critical for ensuring the continuity and integrity of the collected data. For the sake of jointly optimizing the age of information (AoI) and energy consumption, we propose a multi-autonomous underwater vehicle (AUV)-assisted underwater data collection scheme in this paper. The optimization problem is formulated as a mixed integer linear programming (MILP) problem, which is non-deterministic polynomial (NP)-hard. In order to address the problem efficiently, we propose a two-stage method. First, considering the balance of energy consumption and the limitation of sensor communication ranges, we design a cluster-based AUV scheduling data transmission protocol to find a series of hovering points at which the AUVs hover to receive data and schedule data transmissions between the AUVs and sensors. Based on that, a combined heuristic algorithm is proposed to plan AUVs’ trajectories so that the data collection task can be completed properly with a low cost. Simulation results show that the proposed algorithm outperforms three benchmark algorithms in terms of average AoI and collection utility. Specifically, the freshness of information and the collection utility improved by 10.23% and 33.36% on average, respectively. Additionally, the energy consumption of sensor nodes is more balanced, and the network lifetime is extended.

Formation and control of heterocyclic amines and advanced glycation end products in traditional Chinese braised pork belly: The role of food additives - Keyu Lu; Qiaochun Chen; Jiayi He; Qian Zhou; Siqian Li; Mingfu Wang (Food Research International, 2025)

Whether to continue combining carbapenems to treat carbapenem-resistant Acinetobacter baumannii nosocomial pneumonia in critically ill patients: a retrospective efficacy and safety analysis - Cheng Shiqi; Wang Chuhui; Zhang Yijing; Qiu Yulan; Chen Jiaojiao; Chen Keyu; Shi Qindong; Zeng Xiaoyan; Dong Yalin (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Soil with high plant available water capacity can mitigate the risk of wheat growth under drought conditions in southeastern Australia - Keyu Xiang; Bin Wang; De Li Liu; Chao Chen; Fei Ji; Yanmin Yang; Siyi Li; Mingxia Huang; Alfredo Huete; Qiang Yu (European Journal of Agronomy, 2025)

Episodic marine anoxia, primary production, and weathering controls on carbon‑sulfur cycling in the Early Cambrian Yangtze Block - Moïse Luemba; Zhonghong Chen; Keyu Liu; Zhi Chai; Yong Chen; Raphael Matamba; Munezero Ntibahanana (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

PAD resin: An intelligent adsorbent for solving Cr(VI) pollution with real-time feedback and high efficiency - Yuanhao Wang; Guihong Lan; Haiyan Qiu; Keyu Pu; Xiangming Liu; Ling Chen; Bo Xu (Journal of Hazardous Materials, 2025)

Cost effective selective separation of indium and germanium from zinc processing waste leach liquor using D2EHPA-YW100 synergistic system and selective stripping with HCl and NH4F - Chen Wang; Junxian Hu; Keyu Zhang; Shaoze Zhang; Yin Li; Yaochun Yao (Hydrometallurgy, 2025)

Ferric uptake regulator (Fur) in Vibrio mimicus acts as an activator of citrate cycle and oxidative phosphorylation pathways, while enhancing virulence potential - Kun Peng; Keyu Zhou; Qibin Jiang; Yilin Wang; Mingqi Ai; Le Xu; Jiao Wang; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

The impact of organic matter and iron/calcium coupling on phosphorus retention in the hyporheic zone of the Danjiangkou area tributary: Evidence from bonding recognition - Yu Chen; Teng Ma; Liuzhu Chen; Jiabao Sun; Keyu Long; Gongyu Zhou; Weidong Sun (Science of The Total Environment, 2024)

Mapping the susceptibility to freeze-thaw deterioration and regionalization of freeze-thaw environments of earthen sites in China: A preliminary study - Wenwu Chen; Keyu Wang; Qiang Qi; Bobo Jia; Ying Wang; Zhiqian Guo (Science of The Total Environment, 2024)

Spatial mapping of greenhouse gases using a UAV monitoring platform over a megacity in China - Tianran Han; Conghui Xie; Yanrong Yang; Yuheng Zhang; Yufei Huang; Yayong Liu; Keyu Chen; Haijiong Sun; Jietao Zhou; Chang Liu; Junfei Guo; Zhijun Wu; et al. (Science of The Total Environment, 2024)

Reduced-order modeling method for flexibly connected dual-AUV system - Kuo Chen; Zhier Chen; Jiancheng Yu; Kai Ren; Wenkang Jiao; Keyu Chen; Yu Tian; Jie Sun (Ocean Engineering, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Petaloid CoP/FeP Composites: Efficiently bifunctional cathode electrochemical oxygen catalysts for aqueous and Solid-State Zinc-Air batteries - Keyu Chen; Lu Wang; Jilan Long; Fei Zhao; Li Kang (Chemical Engineering Journal, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Effects of seasoning addition and cooking conditions on the formation of free and protein-bound heterocyclic amines and advanced glycation end products in braised lamb - Qiaochun Chen; Keyu Lu; Jiayi He; Qian Zhou; Siqian Li; Hui Xu; Yuting Su; Mingfu Wang (Food Chemistry, 2024)

Boosting activity on CoFe layered double hydroxide by doping and heterostructure as a bifunctional electrocatalyst for efficient overall water splitting - Jian Tang; Junxian Hu; Xuanli Chen; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Shaoze Zhang (Fuel, 2024)

Optimal design of transverse dampers incorporating inherent stiffness effects for stay cable vibration control: A case study with wire rope dampers - Keyu Lai; Wei Fan; Zhengqing Chen; Huawei Niu; Lingfei Ma; Shouying Li (Engineering Structures, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Four-decades of sediment transport variations in the Yellow River on the Loess Plateau using Landsat imagery - Zhiqiang Qiu; Dong Liu; Mengwei Duan; Panpan Chen; Chen Yang; Keyu Li; Hongtao Duan (Remote Sensing of Environment, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

Tectono-sedimentary evolution of the southwestern Tarim Basin in the cretaceous in response to basin-range coupling: New insights from basin and landscape dynamics modeling - Jia Chang; Keyu Liu; Wenfang Yuan; Jianliang Liu; Liqiang Zhang; Cai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Multi objective optimization of recycled aggregate concrete based on explainable machine learning - Shiqi Wang; Peng Xia; Fuyuan Gong; Qiang Zeng; Keyu Chen; Yuxi Zhao (Journal of Cleaner Production, 2024)

Interfacial characteristics and mechanical behavior of geopolymer stabilizers with clay mineral: A molecular dynamics study - Dazhi Wu; Kaiquan Cao; Keyu Chen; Ningning Mao (Applied Clay Science, 2024)

Investigation on catalytic distillation dehydrogenation of perhydro-benzyltoluene: Reaction kinetics, modeling and process analysis - Qinglian Wang; Keyu Le; Yi Lin; Wang Yin; Yixiong Lin; Maria V. Alekseeva; Vadim A. Yakovlev; Anton P. Koskin; Chen Yang; Ting Qiu (Chemical Engineering Journal, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

Enhancing the sewage treatment effect, reducing membrane fouling, and increasing microbial community diversity by a novel biofiller-carrying functional bacteria Rhodococcus sp. CPZ24 in a moving bed biofilm reactor - Peizhen Chen; Dongkai Chen; Bo Yang; Keyu Zhang; Shaopeng Li (Journal of Water Process Engineering, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Biosynthesis of maltodextrin-derived glucan dendrimer using microbial branching enzyme - Yimei Chen; Xiuting Hu; Keyu Lu; Tao Zhang; Ming Miao (Food Chemistry, 2023)

Proteomic profiling of purified avian leukosis virus subgroup J particles - Sheng Chen; Yiming Yan; Liguo Gao; Shuang Gao; Keyu Feng; Hongxin Li; Xinheng Zhang; Weiguo Chen; Feng Chen; Qingmei Xie (Veterinary Microbiology, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Identification of the chemical constituents in Cullen corylifolium ethanolic extract by LC-MS/MS and GC-MS - Hongzheng Wang; Keyu Chen; Rui Xue; Chimengul Turghun; Bo Han (Natural Product Research, 2023)

Plant community and soil available nutrients drive arbuscular mycorrhizal fungal community shifts during alpine meadow degradation - Keyu Chen; Jing Zhang; Muhammad Atif Muneer; Kai Xue; Haishan Niu; Baoming Ji (Fungal Ecology, 2023)

Performance of wire rope damper in vibration reduction of stay cable - Keyu Lai; Wei Fan; Zhengqing Chen; Chao Yang; Zhiwen Liu; Shouying Li (Engineering Structures, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Carbazole and polyhalogenated carbazoles in the marine environment around the Zhoushan Archipelago: Distribution characteristics, environmental behavior, and sources - Zhaochao Deng; Songtao Hu; Leiming Tang; Lingbo Jiang; Junyu He; Keyu Shen; Yongjiu Xu; Rijin Jiang; Tiejun Li; Chunlei Chen; Bairu Chen; Hanghai Zhou; et al. (Journal of Hazardous Materials, 2023)

Recognition of behavior state of Penaeus vannamei based on passive acoustic technology - Maochun Wei; Keyu Chen; Yating Lin; En Cheng (Frontiers in Marine Science, 2022)
Underwater signal processing based on passive acoustic technology has carried out a lot of research on the behavioral sound of underwater creatures and the protection of marine resources, which proves the feasibility of passive acoustic technology for long-term and non-destructive monitoring of underwater biological sound production. However, at present, most relevant research focuses on fish but little research on shrimp. At the same time, as the main economic breeding industry, Penaeus vannamei has a backward industrial structure, in which the level of intelligence needs to be improved. In this paper, the acoustic signals generated by different physiological behaviors of P. vannamei are collected based on passive acoustic technology. Their different behaviors are finally classified and identified through feature extraction and analysis. Meanwhile, the characteristic non-parametric ANOVA is carried out to explore the relationship between the acoustic signals and the behavior state of P. vannamei to achieve the purpose of real-time monitoring of the behavior state of P. vannamei . The experimental results show that linear prediction cepstrum coefficient (LPCC) and Mel-frequency cepstrum coefficient (MFCC) characteristic coefficients are effective in the classification and recognition of different behavioral acoustic signals with interspecific acoustic signals of P. vannamei . Meanwhile, the SVM classifier based on OvR classification strategy can model the acoustic signal characteristics of different underwater biological behaviors more efficiently and has classification accuracy as high as 93%.

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Resistance of blended alkali-activated fly ash-OPC mortar to mild-concentration sulfuric and acetic acid attack - Keyu Chen; Dazhi Wu; Sijia Fei; Chonggen Pan; Xinyuan Shen; Chaoxia Zhang; Juntao Hu (Environmental Science and Pollution Research, 2022)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Identified trans-splicing of YELLOW-FRUITED TOMATO 2 encoding the PHYTOENE SYNTHASE 1 protein alters fruit color by map-based cloning, functional complementation and RACE - Lulu Chen; Wenzhen Li; Yongpeng Li; Xuechao Feng; Keyu Du; Ge Wang; Lingxia Zhao (Plant Molecular Biology, 2019)

Identification of long non-coding RNA p34822 as a potential plasma biomarker for the diagnosis of hepatocellular carcinoma - Cheng Wang; Tianyu Ren; Keyu Wang; Shaogeng Zhang; Shubin Liu; Hu Chen; Penghui Yang (Science China Life Sciences, 2017)

Changes in the long-term hydrological regimes and the impacts of human activities in the main Wei River, China - Hongbo Zhang; Qiang Huang; Qiang Zhang; Lei Gu; Keyu Chen; Qijun Yu (Hydrological Sciences Journal, 2016)

Analysis of S1 gene of avian infectious bronchitis virus isolated in southern China during 2011–2012 - Keyu Feng; Yu Xue; Feng Wang; Feng Chen; Dingming Shu; Qingmei Xie (Virus Genes, 2014)

Molecular characterization, recombinant expression in Escherichia coli and biological activity of (S)-Tetrahydroberberine oxidase from Corydalis saxicola Bunt - Keyu Chen; Ji Ye; Chang Liu; Peng Di; JunFeng Chen; Ying Xiao; HuiLiang Li; WeiDong Zhang (Molecular Biology Reports, 2012)